VD_FINDINFO HC / 2010 / 182 vom 5. März 2010 - VD Tribunal cantonal (2010)
OBLIGATION D'ENTRETIEN, ENFANT, REVENU HYPOTHÉTIQUE, MAXIME OFFICIELLE ET INQUISITOIRE | 276 al. 1 CC, 276 al. 2 CC, 276 CC, 280 al. 2 CC, 285 al. 1 CC, 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC